Influência da morfologia da etringita na expansão de pastas cimentícias contendo nanocarbonato de cálcio - Mendonça, Kelly Roberta Moura (2023)
Understanding and predicting the physicochemical susceptibilities of cementitious materials is a challenge, because they are formed by a mixture of various constituents with different properties. The challenge increases when supplementary materials and additives are used in its composition, such as calcium carbonate, which is commonly used to make cement production more sustainable. There is a growing interest in improving these materials properties, and thereby reducing the influence of undesirable chemical reactions that affect its durability, such as expansion due to delay ettringite formation in already hardened cements. Several studies showed that it is not just about of the ettringite presence and quantity, but that the ettringite morphology and distribution in the microstructure of the cementitious matrix can affect the expansion mechanism of components and construction systems. For the microstructure characterization and analysis it is necessary to stop the hydration reaction. However, there are no conclusive studies on how drying methods affect the evolution of cement hydration phases, mainly for those minorities such as ettringite, even if relevant for durability. Therefore, the work was divided into two parts: 1) To analyze the influence of drying methods on the ettringite morphology and microstructure in cementitious pastes in the presence of calcium nanocarbonate; 2) To analyze the influence of the presence of calcium nanocarbonate on the ettringite morphology and microstructure in cementitious paste and its correlation with expansion. The samples were submitted to x-ray diffraction (DRX), thermogravimetric (TGA/DTG), scanning electron microscopy (SEM), expansion and porosity analyses. Regarding the study 1, it was observed that the presence of nanocarbonate delayed the hydration of the C2S and C3S phases more than it affected the formation of the ettringite phase. The methods involving vacuum better preserved the ettringite crystalline structure, but the methods that included oven were more efficient in stopping the cement hydration reaction. Among the methods involving an oven, drying at 100 °C showed the lowest percentage of the ettringite phase, reflecting in the accentuated dehydration of this phase. It was noted at higher temperatures the presence of less developed crystals, and reduced volume ranges from 0.000-0.150μm3 . In study 2, the highest expansion values at 180 days (0.111%) were found for samples containing excess sulfate ions and with replacement of calcium nanocarbonate. The results indicate that the calcium nanocarbonate presence influences the distribution of ettringite crystals in the paste, the predominance of ettringite crystals in the grasses shape, and also the reduction of the monosulfates sizes, predominating between 0.2-0.3μm, the combination of the factors may have interfered in the expansion process.